2019
DOI: 10.1016/j.numecd.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of beta-blockers, cardiovascular and all-cause mortality in people with hypoglycaemia: An observational study

Abstract: Background and Aims:The association of beta-blockers and their selectivity with mortality and cardiovascular events in patients with and without hypoglycaemia is unknown. Methods and Results:Insulin-treated patients with diabetes were identified within the UK CPRD database. All-cause deaths, cardiovascular events, and hypoglycaemic episodes were captured to assess the interaction between beta-blocker therapy and selectivity with hypoglycaemia. 13682 patients, of which 2036 (14.9%) with at least one hypoglycaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Nevertheless, BBs appeared to be protective of the increase in all-cause and cardiovascular death observed with intensive glycemic control in the ACCORD trial [15]; however BB type and insulin use was not analyzed separately in any of these studies. The present findings are consistent with a recent observational study of outpatients, which found that SBB but not nonselective BB were associated with a possible reduction in mortality in patients with episodes of hypoglycemia [46]. In another study of older nursing home patients discharged after myocardial infarction, there was no difference in mortality between patients prescribed carvedilol and those prescribed metoprolol [28].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, BBs appeared to be protective of the increase in all-cause and cardiovascular death observed with intensive glycemic control in the ACCORD trial [15]; however BB type and insulin use was not analyzed separately in any of these studies. The present findings are consistent with a recent observational study of outpatients, which found that SBB but not nonselective BB were associated with a possible reduction in mortality in patients with episodes of hypoglycemia [46]. In another study of older nursing home patients discharged after myocardial infarction, there was no difference in mortality between patients prescribed carvedilol and those prescribed metoprolol [28].…”
Section: Discussionsupporting
confidence: 92%
“…There have been previous observations on an increase in the risks for cardiovascular events and mortality in beta-blocker-treated than non-beta blocker-treated patients with diabetes mellitus. 25 , 26 , 27 Similarly, beta-blocker was not associated with improved cardiovascular or mortality outcomes in patients without recent MI. 28 , 29 , 30 However, due to the difference in patient profiles and the unique pathophysiology of OSA, our findings should be interpreted within the context of patients with OSA and caution against their generalisation to other populations.…”
Section: Discussionmentioning
confidence: 95%